Saccharides with Different Molecular Weight Affects Crystallization of Calcium Carbonate - Yao, Cheng-Li; Ding, Ai-Min (Asian Journal of Chemistry, 2012)
In this work, soluble starch, chitosan, glucose and sucrose were used to induce the formation of calcium carbonate. The CaCO3 crystals were characterized by scanning electron microscope and Fourier transform infrared spectrograph. The results showed saccharides with different molecular weight had significant influence on the morphology of CaCO3.